Complex oxide catalysts of acrylic acid obtaining by aldol condensation method - Nebesnyi, Roman (Eastern-European Journal of Enterprise Technologies, 2015)
The present work is dedicated to solving the problem of diversification of the raw materials base for acrylate monomers obtaining, first of all acrylic acid. Acrylic acid and its derivatives are bulk products of organic synthesis with a wide range of applications. The main industrial method of acrylic acid production is propylene oxidation. But this method has instable economic indicators as propylene is petroleum origin raw material. It is possible to expand the resource base of acrylic acid production, in particular, by creating a technology of its production by aldol condensation of acetic acid and formaldehyde. The key step of this technology creation is improvement of the process catalysts efficiency. For this aim, new composite oxide catalysts B2O3-P2O5-WO3-V2O5/SiO2 , allowing to obtain acrylic acid with 57.4% yield and formation selectivity 93.7%, have been developed and explored. In this paper the effect of the catalyst components content on the initial reactants conversion and acrylic acid formation selectivity has been researched; the optimal catalyst composition and optimal conditions for the aldol condensation of acetic acid with formaldehyde to acrylic acid have been determined. The high performance of the developed catalyst confirms prospects of using the method of acrylic acid obtaining by aldol condensation as an alternative.